Nature as Honorary Art. (1st August 1998) - Appleton, J.
Abstract : This paper addresses the apparent difficulty experienced by philosophers in applying the methodology of art criticism to the aesthetics of nature and uses the idea of 'narrative' to explore it. A short poem is chosen which recounts the 'narrative' of a simple natural process - the passage of day into night - and this is followed by a simplified critique illustrating how the poem invites questions relating to style, technique, subject, etc., leading to the query whether the art form (poem) can be dispensed with and the subject (nature) be left to tell its own story, using the 'language' of symbolism. The interface between art and science is reviewed particularly in the light of the ideas of John Dewey and what has happened since. The 'symbolism of environmental opportunity' is proposed as the key to crossing the arts/science boundary, and the question is raised whether the distinctiveness of nature is of paramount importance in this context. Various grounds for scepticism are examined, e.g. the danger of drawing inferences about human interaction with nature from the behaviour of other species.